2018
DOI: 10.1002/term.2729
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional tissue culture model of human breast cancer for the evaluation of multidrug resistance

Abstract: Multidrug resistance (MDR) is one of the major obstacles to improving outcomes of chemotherapy in tumour patients. However, progress has been slow to overcome this phenomenon due to the limitations of current cell/tissue models in recapitulating MDR behaviour of tumour cells in vitro. To address this issue, a more pathologically relevant, three-dimensional (3D) culture of human breast cancer cells was developed by seeding the adriamycin-resistant cells MCF-7R in silk-collagen scaffolds. The cultures of the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Hydrogels have been employed in numerous biomedical applications, namely, as scaffolds (Rossi, Santoro, & Perale, ) and controlled release systems (Grijalvo, Mayr, Eritja, & Díaz, ). Additionally, hydrogels can be used as 3D cell culture models to study the cellular behaviour or optimize the dose of pharmacological‐based therapies (Ding et al, ). Hydrogel networks contain a high content of water and a porous structure, allowing the exchange of gas, nutrients, biomolecules, and waste with their surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels have been employed in numerous biomedical applications, namely, as scaffolds (Rossi, Santoro, & Perale, ) and controlled release systems (Grijalvo, Mayr, Eritja, & Díaz, ). Additionally, hydrogels can be used as 3D cell culture models to study the cellular behaviour or optimize the dose of pharmacological‐based therapies (Ding et al, ). Hydrogel networks contain a high content of water and a porous structure, allowing the exchange of gas, nutrients, biomolecules, and waste with their surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we described cancer models engineered to study a variety of tumor types, including those developing in the skin, bladder, and eye tissues. Other important cancer types for which solid 3D tumor models are being developed by various teams include prostate and breast cancers [20,[233][234][235][236][237][238][239][240]. Recent advances for these tumor types include the use of organoids and the incorporation of patient-derived samples (blood derivatives, cells, and/or ECM).…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…In comparison to 2D models, MDA‐MB‐231 cells were less sensitive in 3D due to restricted diffusion because of the physical structure of the scaffold (Talukdar & Kundu, 2012) (studies summarized in Table 3). Also utilizing a naturally derived silk platform, Ding et al (2018) sought to elucidate signaling pathways and other biological factors that contribute to drug resistance in breast cancer. The study found that the DOX‐resistant MCF7 cell line exhibited greater drug efflux due to overexpression of P‐gp and other ABC transporters, along with glutathione conjugation and altered cycle distribution.…”
Section: Scaffold‐based Modelsmentioning
confidence: 99%
“…The study found that the DOX‐resistant MCF7 cell line exhibited greater drug efflux due to overexpression of P‐gp and other ABC transporters, along with glutathione conjugation and altered cycle distribution. The altered cell cycle distribution increased the population of BCSCs (Ding et al, 2018), which has been reported to induce drug resistance (Charafe‐Jauffret et al, 2010). This study also observed the presence of a greater population of dormant cells outlasting treatment, in comparison to 2D culture (Ding et al, 2018).…”
Section: Scaffold‐based Modelsmentioning
confidence: 99%
See 1 more Smart Citation